PENGARUH INTENSITAS PENGGUNAAN MEDIA SOSIAL TERHADAP PERILAKU KEAGAMAAN SISWA KELAS XII SMAN 1 KEDIRI PADA ERA DIGITAL - Diki Endrawan; Akhmad Syahri; Siti Husna Ainu Syukri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the intensity of social media use on the religious behavior of twelfth-grade students at SMAN 1 Kediri in the digital era. This research employed a quantitative approach with a correlational research design. The population of this study consisted of 142 twelfth-grade students of SMAN 1 Kediri in the 2025/2026 academic year. The sample was determined using the Slovin formula, resulting in 105 respondents. Data were collected through questionnaires, observations, interviews, and documentation techniques. The collected data were analyzed using validity tests, reliability tests, normality tests, linearity tests, and simple linear regression analysis with the assistance of statistical software.The results of the study indicate that the intensity of social media use has an influence on students’ religious behavior. This finding is supported by the results of the simple linear regression analysis, which showed a significant relationship between the variable of social media use intensity and students’ religious behavior. The study also revealed that social media can have both positive and negative impacts on students’ religious behavior, depending on the patterns of use, duration of access, and types of content consumed by students. Therefore, proper supervision and guidance are needed so that social media can be utilized positively in supporting students’ religious understanding and character development in the digital era.